Severe hyponatraemia due to high output external biliary drainage corrected with bile refeeding: A case report - Duminda Subasinghe; Preethi Dassanayake; Ravindri Jayasinghe; Sivatharshya Pathmanathan; Vihara Dassanyake; Sivasuriya Sivaganesh (SAGE Open Medical Case Reports, 2024)
Hyponatraemia is an uncommon complication of external biliary drainage. We report on a 62-year-old male with hilar cholangiocarcinoma who developed refractory severe hyponatraemia despite sodium replacement during preoperative external biliary drainage. Nasojejunal bile refeeding restored sodium levels to normal.